Research progress on Wuzi Yanzong pills in the treatment of male infertility - Chiwai Ip; Liang Hong; Yun Tong; Shaoping Li; Jing Zhao (Science of Traditional Chinese Medicine)
Abstract. In recent years, because of changes in lifestyle, social environments, and other factors, male fertility has exhibited a declining trend in various countries and regions, including China. This poses a challenge for the prevention and treatment of male infertility. Wuzi Yanzong pill (WZYZP) is a renowned Chinese medicinal formula utilized for the treatment of male infertility and boasts a long history of use in this context. This article summarized the treatment approaches used in both Chinese and Western medicine for male infertility, along with the research advancements pertaining to the analysis of Chinese medical theory, pharmacological effects, bioactive ingredients, and the establishment of quality control standards for WZYZP in the treatment of male infertility, aiming to provide references for research related to the mechanism of action, identification of active ingredients, and clinical application of WZYZP in the treatment of male infertility.